Documentation of Ornamental Flora of Balkumari College - Das, Manoj K.L. (Journal of Balkumari College, 2020)
The practice of decorating home Garden, temples, public parks, hotels, college and other places by ornamental plants have been known from ancient time. These plants are advantageous as they are so applicable for aesthetic purpose in landscaping and also provide fresh air to breathe. The study was destined to document about the circumstances of ornamental plants of Balkumari College. Information's were collected by direct observation questionnaires, interview, and photographic collection. 54 ornamental plants were documented belonging to 38 families. Out of them, 26 plants belong to the herbs .13 plants were shrubs and 10 plants were documented as trees whereas 5 plants were climbers. As 22 plants had entire plants as ornamental values, 28 plants are documented as flowers, as ornamental parts 3 plants had leaves as ornamental part only one plant had fruit, as ornamental part. Out of 54 plants, 42 plants were reported as perennial and 12 plants as annual growing pattern out of all documented plants, 39 plants were available throughout the year 14 plants were cultivated in winter season and only one plant cultivated in the summer season.